Historical meals, archaeobotanical foodways: expressions of colonialism and nationalism in Quebec City - Bouchard-Perron, Julie-Anne (2017)
Between 1542 and 1867, Quebec City area (Quebec, Canada) was briefly occupied by French explorers, colonised by French settlers and conquered by English forces about a century before becoming part of the Dominion of Canada. My thesis explores the emergence and development of colonialism and nationalism in the region following these changing social, political and economic circumstances. Instead of focusing on discourse, I draw attention towards lived experience by addressing these ideologies through the ways they were intertwined with local foodways, as reconstructed on the grounds of archaeobotanical data dating between 1542 and 1867. More specifically, I investigate how the social and biological biographies of consumed plants bound colonial communities to Europe, the Native world, and local wilderness through time, and in doing so expressed and contributed towards sustaining colonialist and nationalist ideologies. This approach sheds light on the lasting attachment of local colonists to Old World traditions and on how this predilection impacted the selection of wild local plants consumed. It further reveals a widespread disregard for Native populations whose foodstuffs were scantly, if at all, consumed. It is also possible to document the mechanisms which guided the introduction of wild indigenous plants into local menus and the tightening grip of the community over regional environments. The discussion finally underlines how these different propensities paved the way for a homogenisation of culinary habits decades before the publication of the first regional cookbooks and the birth of the nation.